A Gene Atlas of the Mouse and Human Protein-Encoding Transcriptomes - Su, Andrew I.; Wiltshire, Tim; Batalov, Serge; Lapp, Hilmar; Ching, Keith A.; Block, David; Zhang, Jie; Soden, Richard; Hayakawa, Mimi; Kreiman, Gabriel; Cooke, Michael P.; Walker, John R.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2004)
The tissue-specific pattern of mRNA expression can indicate important clues about gene function. High-density oligonucleotide arrays offer the opportunity to examine patterns of gene expression on a genome scale. Toward this end, we have designed custom arrays that interrogate the expression of the vast majority of protein-encoding human and mouse genes and have used them to profile a panel of 79 human and 61 mouse tissues. The resulting data set provides the expression patterns for thousands of predicted genes, as well as known and poorly characterized genes, from mice and humans. We have explored this data set for global trends in gene expression, evaluated commonly used lines of evidence in gene prediction methodologies, and investigated patterns indicative of chromosomal organization of transcription. We describe hundreds of regions of correlated transcription and show that some are subject to both tissue and parental allele-specific expression, suggesting a link between spatial expression and imprinting.